Delayed Lysis with a Mutant of Salmonella Bacteriophage P22 - Cohen, Larry W. (1969)
A mutant of bacteriophage P22 (Lys(−)) was isolated which shows a plaque morphology on mixed plates comparable to the r(+) plaques of the T-even phages. When Lys(−) and normal Lys(+) plaques are juxtaposed on a petri dish, the Lys(+) plaque exhibits a flat side adjacent to the Lys(−) plaque. The mutant is identical to P22 under an electron microscope, is inactivated at the same rate by antiserum and heat, and has the same kinetics of attachment. It does not plate on Salmonella lysogenic for phage P22 nor on strain St/22. In liquid culture, the lysis of mutant infections in M9CAA medium is delayed between 20 and 40 min. Cells mixedly infected in M9CAA with Lys(−) and Lys(+) phage lyse later than Lys(+)-infected cells and even later than Lys(−)-infected cells. In unsupplemented M9 medium, however, mixedly infected cells again lyse later than Lys(+)-infected cells, but Lys(−)-infected cells require more than 3 hr to lyse. In supplemented and unsupplemented M9 media, intracellular phage development and endolysin synthesis proceed in Lys(−) infections at least as rapidly as in Lys(+)-infected cells. In diluted infections, the latent and eclipse periods of Lys(−) and Lys(+) infections are indistinguishable. The possible mechanisms involved in the control and timing of lysis are discussed.